Role of CD4 endocytosis in human immunodeficiency virus infection. - Pelchen-Matthews, A (1995)
We have analyzed the role of CD4 endocytosis in human immunodeficiency virus (HIV) entry by measuring the infection of HeLa cells expressing various CD4 constructs with endocytosis rates of between 0.2 and 30%/min in a quantitative infectious focus assay. For a number of laboratory-adapted HIV-1 and HIV-2 strains, the highest levels of infection were found on cells with very limited CD4 endocytosis, while cells with efficient CD4 uptake were only poorly infectable, suggesting that CD4 internalization is not required for HIV entry. This was confirmed in a modified assay involving prebinding of HIV-1LAI to HeLa-CD4 cells at 4 degrees C, synchronized virus entry during warming to 37 degrees C, and neutralization of virions remaining at the cell surface with anti-V3 loop antibodies. Warming cells in hypertonic medium inhibited CD4 endocytosis but did not affect the rate or the extent of infection. These studies confirm that HIV infection does not require endocytosis and that laboratory-adapted virus strains can enter HeLa-CD4 cells by fusion at the plasma membrane.